Blepharoplasty in Involutional Spastic Lower Lid Entropion - I. V. Ivolgina (Oftalʹmologiâ)
Background. The eyelids are movable folds that protect the eyeball from external influences and carry out a supporting function. A misalignment of the eyelids can seriously effect on the ocular function.Purpose. To evaluate the effectiveness of surgical treatment of spastic lower lid entropion.Patients and methods. The results of treating patients with eyelid entropion for the period from 2014 to 2021 were analyzed — 66 people, 85 operations. All patients with eyelid entropion underwent a standard ophthalmological examination and additional studies, which revealed the presence of a spastic component. The pathogenetically substantiated methods of surgical treatment were performed.Results and discussion. In all 69 cases, where operations were performed according to the Wheeler and Callahan method — the lower eyelid was in the correct position, changing the direction of tension of the circular muscle and the Riolan’s muscle, creating a duplicate of the muscles. The retractor was strengthened, which ensured the correct position of the eyelid. In 16 cases in recurrent entropion and the presence of blepharospasm caused by corneal changes, surgery was performed according to the Meek method. In the early period, in all cases, hyper effect was observed. In the late period, the hyper effect persisted in 4 cases (25.00 %), but the patients refused reoperation.Conclusions. Determination of the parameters of the lower eyelid state during examination makes it possible to identify the reasons for the development of entropion, the presence of a spastic component MRI or CT examination allows assessing the condition of the eyelid retractor objectively. In patients with spastic entropion, Wheeler and Kallahan surgeries that eliminate the spastic component provide a stable result. In patients with spastic recurrent entropion, accompanied by blepharospasm, the Meek’s surgeries in all cases provide a stable result. The disadvantage of this operation is the presence of hyper effect in 100 % of cases in the early period, which persisted in the late postoperative period in 25 % of cases.